Evaluation of genetic diversity of Indigenous poultry (Khukhri) found in Chotanagpur Plateau of Jharkhand - AGARWAL, SEEMA; KUMAR, RAVINDRA; NASKAR, SOUMEN; CHANDRA, SUBHASH; SHEKHAR, SUDHANSHU (The Indian Journal of Animal Sciences, 2026)
Indigenous poultry farming plays an important role in livelihood and nutritional security of rural and tribal populations of Jharkhand. The present study was undertaken to evaluate the phenotypic performance and genetic diversity of Khukhri chicken of the Chotanagpur plateau. A field survey was conducted on 270 households covering 540 birds. Phenotypic characterization revealed predominance of mixed plumage with yellow shank colour (85.56%) and uniform red earlobe, comb and white skin. However, variability in comb type was observed with single comb (≈52%) being predominant. Adult body weight of males and females averaged 1552.18 ± 27.46 g and 1182.04 ± 14.30 g, while shank length was 9.85 ± 0.08 cm and 8.73 ± 0.05 cm, respectively. Genetic diversity was assessed using RAPD markers on 50 birds. Out of 22 primers, 16 produced polymorphic bands generating 172 bands, of which 168(97.67%) were polymorphic. Nei’s gene diversity ranged from 0.28 ± 0.01 to 0.29 ± 0.01, and Shannon’s information index ranged from 0.43 ± 0.01 to 0.44 ± 0.01 across populations. The study indicated moderate genetic variability within Khukhri chicken populations. However, the observed variability in comb type suggested that further studies focusing on uniform sub-populations (particularly single-comb birds) are necessary for breed standardization and conservation planning.